Low haemoglobin levels increase unilateral spatial neglect in acute phase of stroke - Luvizutto, Gustavo Jose [UNESP] (2014)
Objective: The objective of this study was to evaluate the relationship between unilateral spatial neglect (USN) and haemoglobin (Hb) level in acute phase of stroke. Method: Cross-sectional study was performed after right hemisphere ischemic stroke. Independent variable: Hb level (mg/dL); Outcome: USN; Potential confounding factors: Age, National Institutes of Health Stroke Scale (NIHSS), and glycaemia (mg/dL); Characterization variables were obtained from electronic medical records, Hb, mean corpuscular volume (MCV) and glycaemia by laboratory exams, and USN by cancellation and bisection tasks. The relationship between Hb and USN was assessed by Spearman correlation and linear regression model. Results: 40 individuals were evaluated; it was observed that the higher the Hb level, the better the USN test performance, with the two being negatively correlated. There was no significant correlation between VCM level and USN performance. Conclusion: Low hemoglobin levels may indicate a worse performance in USN cancellation and bissection tests in acute phase of stroke.